VD_FINDINFO Décision / 2011 / 644 vom 10. Oktober 2011 - VD Tribunal cantonal (2011)
MISE EN LIBERTÉ PROVISOIRE, RISQUE DE FUITE, RISQUE DE RÉCIDIVE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. c CPP (CH), 233 CPP (CH)